Adsorption of heavy metal using mesoporous silica / Elham O.S.J ... [et al.] - Elham, O.S.J; Sabari, N.A; Roslan, A.A; Mohamad Zamri, N.A.I
Heavy metals such as Pb, Zn, Ni, Cr are discharged into water from various industries which they can be toxic or carcinogenic in nature and can cause severe problems for humans and aquatic ecosystems. The pollution of water is now being an environmental problem of global concern and efforts are being made for their efficiency of removal using various natural and synthetic materials. To overcome the problems, the present study was undertaken to explore the efficiency of heavy metal adsorption by mesoporous silica at the concentration of 30 ppm of Zinc and Lead. Further experiments have been carried out by using Fourier Transform-Infrared spectroscopy (FTIR) and Inductively Coupled Plasma spectrometry (ICP-AES). The result obtained from the study shows that the ability adsorption of Pb2+ ion was significantly higher than others metal ions which heavy metal removal percentage was 74.93% compared to Zn2+ that was 74.36%. In addition, as the contact time increases and more dosage of adsorbent added, it shows the increment of percentage reduction of heavy metal by using mesoporous silica. Thus, it can be proved that adsorption process is widely used for the removal of heavy metals from wastewater because of its low cost, availability and eco-friendly nature